A PCL/cellulose coil-shaped scaffold via a modified electrohydrodynamic jetting process - Young Eun Choe; Geun Hyung Kim (Virtual and Physical Prototyping, 2020)
Scaffolds are regarded as a key factor for tissue engineering as they provide a three-dimensional structural frame for host cells to attach, proliferate, and differentiate. Recently, 3D bioprinting has enabled the quick and versatile fabrication of various architectures of micro/macroscale scaffolds, but there remain obstacles to successful tissue regeneration, such as large strut diameter and simple pore geometry and distribution. To overcome these deficiencies, we propose a new scaffold, which was fabricated using polycaprolactone (PCL)/cellulose and electrohydrodynamic jetting (EHDJ), composed of a spring-shaped strut and controllable macro/micropores. In this work, PCL provided reasonable mechanical strength and synergistic effects with cellulose, which homogeneously covered the PCL surface. Furthermore, the homogeneously distributed cellulose promoted meaningful cellular activities. By manipulating various processing parameters, we fabricated a stable coil-shaped scaffold and evaluated it for physical characteristics and in vitro cellular activities, including osteogenic activities, using MG63 cells. Consequently, the coil-shaped scaffold exhibited a significantly higher degree of cellular activity than the controls (PCL coil-shaped scaffold and PCL coil-shaped scaffold dipped in cellulose). Based on our results, the coil-shaped structure could represent a scaffold with high potential for use in hard tissue regeneration.